Analysis of Backward Methods for Determining Trip Attraction Model on Commercial and Service Area in Sukun Raya Road, Banyumanik, Semarang. Issue 1 (January 2020) - Basuki, Y; Rahayu, S; Rahmawati, N W
Abstract: One strategy for sustainable development planning is to minimize future problems. To minimize future problems modelling is needed to predict future conditions based on current characteristics. Commercial areas located in the Sukun Raya Road Corridor, Banyumanik Subdistrict are small-scale trade and trade areas in the central government area. Development of trade and small-scale areas must be supported by the existence of a trip attraction model that can be used to predict future trips in the region. The aim of this article is to develop trip attraction model. The model is multiple linear regression analysis. Multiple linear regression analysis using the backward method shows that there is a relationship between the Y variable which consists of the total visitor's attraction (pcu/hour) with the independent variable X2 (store area), X3 (store parking area), and X4 (sales income) . The relationship between the dependent variable Y with the independent variables X2, X3, and X4 is very influential with the value R 2 0.820 with the resulting equation model Y = -1.504 + 0.021 X2 - 0.085 X3 + 9.847E-7 X4 .This model can be used to estimate and anticipate trip attraction in small-scale commercial and services areas based on store area plans, large parking areas, and sales income. This model can be used as a consideration in planning and structuring commercial areas small scale to anticipate transportation problems because they contribute to the flow of traffic in Sukun Corridor.